-23=-t

Simple and best practice solution for -23=-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23=-t equation:


Simplifying
-23 = -1t

Solving
-23 = -1t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add 't' to each side of the equation.
-23 + t = -1t + t

Combine like terms: -1t + t = 0
-23 + t = 0

Add '23' to each side of the equation.
-23 + 23 + t = 0 + 23

Combine like terms: -23 + 23 = 0
0 + t = 0 + 23
t = 0 + 23

Combine like terms: 0 + 23 = 23
t = 23

Simplifying
t = 23

See similar equations:

| b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 | | -8x-9+5x=-9x+3 | | x+3=5x+2 | | 4.9t^2+2.14t+42=0 | | 5F-9C=120 | | 3/2*16*1/2 | | 7/2*16*-1/2 | | .5x-2.3=0.7 | | 3x+7x+4=2x-6 | | -21.15=m-6.33-6.7m | | 15/2*64*-1/2 | | -8a-b-(-6c)-2a-b-5c=0 | | x-3/10-8=3x+2 | | 6-2x+7-3x=12 | | 2*6*w+2*w*8+2*6*8=208 | | 9x-7=9(x-5) | | 15/2((64)-1/2) | | -2c=pm^2-n | | -(x+2)=-18-x | | X-5/3=5/4 | | x/5=-23 | | 1/2(0.75-0.25) | | -8x+16=-3x-4 | | 3(43)-8+43+2(98.5)-17=180 | | 7d-12+3=18 | | 32-8k=-6+6(-7-8k) | | 6r^2+13r-63=0 | | 1.00/2.00(0.75-0.25) | | 8p-11=5 | | 12x+17=18x-17 | | .50x+.50(100)=.25(140) |

Equations solver categories